209k views
1 vote
What is equivalent to 6x + 4(1 - x)

User Dan Patil
by
6.7k points

1 Answer

3 votes

Given the expression;


\begin{gathered} 6x+4(1-x) \\ We\text{ shall expand the parenthesis on the right of the expression} \\ =6x+\lbrack(4*1)-(4x) \\ =6x+4-4x \\ \text{Collect all like terms;} \\ =6x-4x+4 \\ =2x+4 \\ \text{Next step, you factorize the expression (2 is a common factor)} \\ =2(x+2) \end{gathered}

The equivalent expression therefore is 2(x + 2), that is, the third option

User BrianMiz
by
5.4k points